2016
DOI: 10.4067/s0718-221x2016005000049
|View full text |Cite
|
Sign up to set email alerts
|

Natural durability of Cedrus atlantica wood related to the bioactivity of its essential oil against wood decaying fungi

Abstract: The Atlas cedar, Cedrus atlantica is a resinous species of Pinaceae originated from North Africa and well known for its noble timber. This work was conducted to assess the natural durability of its wood, to study the chemical composition of essential oil extracted from its sawdust wood and to test the bioactivity of this essential oil against four wood decaying fungi: Gloeophyllum trabeum, Oligoporus placenta, Coniophora puteana and Trametes versicolor. The assessment of natural durability of wood was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 19 publications
1
38
0
2
Order By: Relevance
“…Essential oils have benefits such as they can provide safe and environmentally friendly preservatives. They are effective against bacteria (Burt 2004, Wong et al 2008), fungi (Carlton et al 1992, Mahmoud 1994, Voda et al 2003, Wang et al 2005, Singh and Singh 2012, Boulogne et al 2012, Fidah 2016) and insects (Isman et al 2011, Fatima andMorrell 2015). Some studies were done on the efficacy of essential oils against moulds (Voda et al 2003, Yang and Clausen 2006, Pánek et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils have benefits such as they can provide safe and environmentally friendly preservatives. They are effective against bacteria (Burt 2004, Wong et al 2008), fungi (Carlton et al 1992, Mahmoud 1994, Voda et al 2003, Wang et al 2005, Singh and Singh 2012, Boulogne et al 2012, Fidah 2016) and insects (Isman et al 2011, Fatima andMorrell 2015). Some studies were done on the efficacy of essential oils against moulds (Voda et al 2003, Yang and Clausen 2006, Pánek et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The decay resistance of wood depends on several factors such as the species of wood, its moisture content and chemical composition (e.g. the extractive content), climatic conditions and its intended use (Delucis et al 2016, Fidah et al 2016. Therefore, it needs to be protected from biodegradation using chemical preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…For Cedrus atlantica (2) , the three individual components found with the highest percentage were alpha-cedrene (31.4%), cedrol (23.52%), and cis-thujopsene (20.45%). From other studies, one reported that the three individual components found with the highest percentage were alpha-pinene (14.85%), himachalane (10.14%), and beta-himachalene (9.89%) [38], a different study reported E-gamma-atlantone (19.73%), E-alpha-atlantone (16.86%), and 5-isocedranol (11.68%) [39], while another reported limonene (29.18%), myrcene (16.9%), and ocimene + alpha-pinene (18.6%) [40]. For all studies, the essential oil was collected in or around Morocco via hydrodistillation.…”
Section: Discussionmentioning
confidence: 99%